2002
DOI: 10.1007/s00403-002-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human neutrophil peptide-1 on the expression of interstitial collagenase and type I collagen in human dermal fibroblasts

Abstract: Human neutrophil peptide-1 (HNP-1), a defensin with antimicrobial properties, is also thought to promote wound healing. To elucidate the mechanism by which wound healing is facilitated by this factor, we investigated the effect of HNP-1 on the expression of interstitial collagenase (matrix metalloproteinase 1, MMP-1), collagen types I and III, and tissue inhibitor of metalloproteinase 1 (TIMP-1) by cultured fibroblasts by means of RT-PCR and ELISA. Our results showed that synthetic HNP-1 increased the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 21 publications
5
29
0
4
Order By: Relevance
“…Both neutrophil a-defensins and LL-37 have been shown to affect epithelial wound repair. Specifically, neutrophil defensins are mitogenic for fibroblasts [39] and increase collagen type I and III expression in both dermal and corneal fibroblasts [40,41], suggesting that increased levels of a-defensins may contribute to tissue fibrosis. Therefore, the higher levels of a-defensins in transplant recipients with BOS may be associated with an exaggerated repair response to airway damage.…”
Section: Discussionmentioning
confidence: 99%
“…Both neutrophil a-defensins and LL-37 have been shown to affect epithelial wound repair. Specifically, neutrophil defensins are mitogenic for fibroblasts [39] and increase collagen type I and III expression in both dermal and corneal fibroblasts [40,41], suggesting that increased levels of a-defensins may contribute to tissue fibrosis. Therefore, the higher levels of a-defensins in transplant recipients with BOS may be associated with an exaggerated repair response to airway damage.…”
Section: Discussionmentioning
confidence: 99%
“…Many of those cationic amphipathic molecules have immunomodulatory activities, modulating inflammation and enhancing protective responses, including phagocytic recruitment and deficiency, as well as angiogenesis and wound repair (11,12). Structurally, HDPs are highly diverse, and their primary sequence can be used as the templates for the development of synthetic peptides with optimal immunomodulatory and/or antimicrobial activity to influence future clinically relevant therapeutic guidelines (13).…”
mentioning
confidence: 99%
“…In contrast, the expression of matrix-metalloproteinase-1 was decreased. The authors suggest that HNP-1 may promote wound repair by enhancing extracellular matrix deposition (153). Another study showed mitogenic activity of HNPs in epithelial and fibroblast cell lines in vitro (154).…”
Section: Host Defense Peptides In Woundsmentioning
confidence: 99%
“…Oono et al (153) showed that synthetic HNP-1 increases the expression of pro-collagen mRNA and protein in dermal fibroblast cultures. In contrast, the expression of matrix-metalloproteinase-1 was decreased.…”
Section: Host Defense Peptides In Woundsmentioning
confidence: 99%